FUR GENE EXPRESSION AND ITS RELATION WITH IRON-RESPONSIVE GENES IN PSEUDOMONAS AERUGINOSA ISOLATES FROM WOUNDS AND BURNS - Sattar, Uhud Abdul; Resha, Rasmiya A. Abu (Eastern Ukrainian Medical Journal, 2024)
Introduction. Pseudomonas aeruginosa is known as opportunistic and results in a variety of infections by the acquisition of iron from the host by iron-responsive genes, which are known as Pvd and Pch. Expression of these genes is controlled by a gene known as Fur, which is responsible for the regulation of genes mentioned above under iron availability conditions. This research aimed to study the relationship between Fur and iron-responsive genes in Pseudomonas aeruginosa under iron availability in order to use the iron in different concentrations to prevent and inhibit infections by P. aeruginosa.Materials and methods. Forty isolates were collected and identified by culture and biochemical tests based on growth characteristics on ordinary culture media like blood, macConkey and cetrimide agar. Colonies of isolates appeared as large, irregular beta-hemolytic on blood agar, while they appeared colorless with a positive oxidase test on macConkey, and on a cetrimide agar, they appeared greenish. A biochemical test was achieved to confirm the pathogen is P. aeruginosa; results showed indol negative, citrate positive, urease negative, motility positive, and lastly, no fermentation of glucose and lactose. PCR was also used to confirm these isolates as P. aeruginosa by detection of 16SrRNA as a reference gene. Different iron concentrations were prepared by equation c1v1=c2v2; then, the bacteria were cultured in sterile brain heart infusion with different iron concentrations and incubated for 24 h at 37 ℃. qPCR was performed on these isolates to assess the effect of Fur on gene expression of target genes under iron availability conditions.Results. Results showed that iron-responsive genes were affected by the Fur gene in some isolates but not affected in others. We conclude from these results that the Fur gene controls the gene expression of iron-responsive genes under a universal environment, and other factors are also required to regulate target genes, such as affinity, stability, and quality of the interaction between Fur and DNA and the structure of Fur boxes.Conclusion. The prevalence of nosocomial infections caused by P. aeruginosa is increasing in Iraqi hospitals. Iron and Fur gene play an important role in the pathogenicity of bacteria because, under replete iron conditions, the Fur gene acts as an ap-oppressor and binds with iron, which acts as a co-pressor to repress expression of iron-responsive genes and vice versa to maintain the bacterial life and keeping iron homeostasis within bacteria.